Linear Parameter-Varying (LPV) Buckling Control of an Imperfect Beam-Column Subject to Time-Varying Axial Loads - Schaeffner, Maximilian; Platz, Roland (Model Validation and Uncertainty Quantification, Volume 3, 2017)
In this paper, active buckling control of an imperfect slender beam-column with circular cross-section by piezo-elastic supports and Linear Parameter-Varying (LPV) control is investigated experimentally. The beam-column is loaded by a time-varying axial compressive load resulting in a lateral deflection of the beam-column due to imperfections. A finite element model of the beam-column under axial load is designed as an LPV system. A reduced and augmented modal model is used to design a quadratically stable gain scheduled LPV control. The control is implemented in an experimental test setup and the maximum bearable loads of the beam-column are obtained. Two cases are tested: with and without LPV control or, respectively, active and passive configuration. With the proposed active LPV buckling control it is possible to compensate the influence of beam-column imperfections and to compensate uncertainty in mounting and loading that in passive configuration without LPV control may lead to early buckling. Eventually, the maximum bearable axial compressive load is increased above the theoretical critical buckling load.